Effects of high-intensity interval training in school on the physical performance and health of children and adolescents: a systematic review with meta-analysis - Bauer, Nikolai; Sperlich, Billy; Holmberg, Hans-Christer; Engel, Florian (Sports medicine - open, 2022)
Performance of high-intensity interval training (HIIT) by children and adolescents improves physical and health-related fitness, as well as cardiometabolic risk factors.